Análise das tensões nodais em blocos de concreto armado apoiado sobre duas estacas metálicas - Tomaz, Marco Aurélio (2018)
The pile caps can be dimensioned using, preferably, plastic models (struts-and-tie) and models based on flexion theory. The objective of this work was to analyze and discuss the nodal stresses that arise in pile caps when piles are used in steel profile. Firstly, an experimental and theoretical analysis was applied the different stress calculation models in experimental test of several researchers in order to observe the differences between the presented models. With the value of the operating tensions, both in the upper nodal zone and in the lower nodal zone, it is possible to compare with the limits values recommended by the current norms and by researches. The calculation models studied showed differences between then and, as a result, a critical analysis of these results was carried out and a new limit for the verification of the nodal tensions near the upper nodal zone is suggested. Four pile caps were experimentally tested on two piles where the variables were the inlay of the piles in the pile caps and the adoption of a welded steel plate at the top of the steel profile. The calculation of the stresses in the lower nodal zone depends on the cross-sectional area of the pile and it is not consistent to apply the available formulations to verify such stresses since the area of the steel profile is considerably smaller than the area of a pile in reinforced concrete. However, the tensions in the lower nodal area were shown to be coherent when a pile area called Collaborating Area was considered larger than the steel profile. This area considers, in addition to the steel profile area, the concrete confined between the profile flaps. The test showed that the pile caps present behavior similar to the behavior presented by pile caps supported by pile of reinforced concrete. Furthermore, it was possible to confirm two hypotheses presented by order researchers: the force acting on the ties is not constant and the pile was subjected to flexo-compression.